Selection of Sustainable Suppliers Using the Fuzzy MARCOS Method - Puška, Adis; Stević, Željko; Stojanović, Ilija (Current Chinese Science, 2021)
Background: Selection of Sustainable Suppliers is a key term in sustainable supply chain management. This is the reason to choose the supplier who will support the company to implement sustainability in its business, especially in the supply chain. Objective: The aim of this paper is to establish a new innovative model for decision-making based on a fuzzy approach. Methods: This decision-making problem is solved by applying multi-criteria decision-making since there are several criteria according to which a decision should be made: economic, social, and environmental. In order to make the final decision on the supply chain better and safer, the social criteria were modified in this paper, adding ethical criteria. The example with modified social criteria in this paper was shown on the example of the company
Keywords: MCDM